The Causes of Intraoperative Pain among Elective Caesarean Section Patients under Sub-Arachnoid Block at the Tamale Teaching Hospital - , Samuel Kwame Amoako Asirifi; , Keren-Happuch Twumasiwaa Boateng; , Iddrisu Baba Yabasin (Archives of Current Research International, 2024)
Background: Intraoperative pain is a possible complication of neuraxial anaesthesia for caesarean delivery. Possible causes of intraoperative pain following caesarean section under spinal anaesthesia have been proposed. The potential consequences include inadequate anaesthesia, nerve injury during needle insertion, manipulation of internal organs during surgery, and psychological factors such as anxiety and fear. This study was conducted to assess the causes of intraoperative pain among patients undergoing elective caesarean section under sub-arachnoid block at the Tamale Teaching Hospital. Methods: A descriptive cross-sectional research design was employed in this study. A total of 55 women who have had elective caesarean section under sub-arachnoid block were selected for the study. Data was collected using a structured questionnaire and analysed with the SPSS. Results: Findings from the study showed a high incidence of intraoperative pain among women during elective caesarean section under sub-arachnoid block (96.4%). These were mainly sharp and aching pain. However, the levels of the pain experienced intraoperative were mild (52.7%) and moderate (43.6%). Increased length of time spent during surgery and ineffectiveness of medications/ injections given to prevent pain were the main factors contributing to intraoperative pain among patients during elective caesarean section under sub-arachnoid block. Conclusions: The study found a substantial incidence of intraoperative pain during caesarean delivery. To mitigate intraoperative discomfort and enhance the overall surgical experience for patients having elective CS, it is crucial to address these issues by employing optimised anaesthesia techniques, implementing effective pain management measures, and utilising preoperative psychological therapies.